Bioenergetic markers in skin fibroblasts of sporadic amyotrophic lateral sclerosis and progressive lateral sclerosis patients. Issue 4 (21st August 2014) - Kirk, Kathryne; Gennings, Chris; Hupf, Jonathan C.; Tadesse, Saba; D'Aurelio, Marilena; Kawamata, Hibiki; Valsecchi, Federica; Mitsumoto, Hiroshi; for the ALS/PLS COSMOS Study Groups; Manfredi, Giovanni
<x xml:space="preserve">Abstract</x> Energy metabolism could influence amyotrophic lateral sclerosis (ALS) and progressive lateral sclerosis (PLS) pathogenesis and the response to therapy. We developed a novel assay to simultaneously assess mitochondrial content and membrane potential in patients' skin fibroblasts. In ALS and PLS fibroblasts, membrane potential was increased and mitochondrial content decreased, relative to healthy controls. In ALS higher mitochondrial membrane potential correlated with age at diagnosis, and in PLS it correlated with disease severity. These unprecedented findings in ALS and PLS fibroblasts could shed new light onto disease pathogenesis and help in developing biomarkers to predict disease evolution and the individual response to therapy in motor neuron diseases. Ann Neurol 2014;76:620–624